Reliance Jio: the Patanjali of Telecommunication (â€œThink Big, Think Fast, Think Ahead. an Idea is No Oneâ€™s Monopolyâ€- Dhirubhai Ambani) - M. Siva Krishna Raju, Dr.; Sri Krishna Chaturya, V.; A.Krishna Sudheer, Dr. (International Journal of Engineering and Technology, 2018)
India is a developing country and it is a long term dream of every Indian to see India as a developed country. For a country to be developed, all the sectors needs to be developed. One of the essential sectors that need focus and immediate concentration is the telecommunication sector. Not only from the point of development, Telecommunication sector plays a very important role in India, as its is the sector that is entrusted with the responsibility of connecting Indians. Indians are social people and they always likes to be in touch with their fellow people and they are very good in networking with other groups and sects in and around them. They thus rely on telecommunication sector and now a days mobile phones are the essential commodities for every person. This has become a major sector with many foreign players entering into it. This sector has further future growth with the emergence of 4G and 5G technologies. All is well with this sector until the entry of RELIANCE JIO in to this. This entry has shaken the whole India and particularly the telecommunication sector. This has become the talk of the world. So, this paper in detail aims to enlighten the readers on the telecommunication sector in India with special emphasis on Reliance Jio and its impact on the Indian Telecommunication sector.Â